Hydrolytic cleavage of N6-substituted adenine derivatives by eukaryotic adenine and adenosine deaminases - Pospísilová, Hana; Sebela, Marek; Novák, Ondrej; Frébort, Ivo (Bioscience reports, 2008)
Homogeneous adenine deaminases (EC 3.5.4.2) from the yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe and a putative ADA (adenosine deaminase; EC 3.5.4.4) from Arabidopsis thaliana were obtained for the first time as purified recombinant proteins by molecular cloning of the corresponding genes and their overexpression in Escherichia coli. The enzymes showed comparable molecular properties with well-known mammalian ADAs, but exhibited much lower k(cat) values. Adenine was the most favoured substrate for the yeast enzymes, whereas the plant enzyme showed only very low activities with either adenine, adenosine, AMP or ATP. Interestingly, the yeast enzymes also hydrolysed N6-substituted adenines from cytokinins, a group of plant hormones, cleaving them to inosine and the corresponding side chain amine. The hydrolytic cleavage of synthetic cytokinin 2,6-di-substituted analogues that are used in cancer therapy, such as olomoucine, roscovitine and bohemine, was subsequently shown for a reference sample of human ADA1. ADA1, however, showed a different reaction mechanism to that of the yeast enzymes, hydrolysing the compounds to an adenine derivative and a side chain alcohol. The reaction products were identified using reference compounds on HPLC coupled to UV and Q-TOF (quadrupole-time-of-flight) detectors.The ADA1 activity may constitute the debenzylation metabolic route already described for bohemine and, as a consequence, it may compromise the physiological or therapeutic effects of exogenously applied cytokinin derivatives.
Keywords: Adenosine; Arabidopsis Proteins; Saccharomyces cerevisiae Proteins; hydrolýza; Saccharomyces cerevisiae; puriny; adenosin; rekombinantní proteiny; Recombinant Proteins; cytokininy; Cytokinins; proteiny huseníčku; adenosindeaminasa; Hydrolysis; Purines; Aminohydrolases; aminohydrolasy; Arabidopsis; Adenosine Deaminase; Saccharomyces cerevisiae - proteiny